(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
The internationalization of extension is a function that latinamerican universities have been promoting to favor technical, scientific and social development with the community. It is a dialogue between knowledge of the community and knowledge developed by the members of the University. The experience of the National University of La Pampa with the Federal University of San Carlos Brazil (UFSCar) is communicated, in an International Extension Action (AIdeE) related to the exchange of popular knowledge and scientific discourse between both countries on vaccination in the COVID 19 pandemic. In this action, knowledge from different cultures was exchanged, sharing experiences and analyzing scientific knowledge that was considered beneficial by the participants, and that was disseminated in the community context where it was developed. The shared experience between the two universities is an important precedent to promote future extension internationalization actions, since it enriches teachers, students, and the community in general.